Design and Implementation of Ultraviolet Light Control on Corn Fodder Using Fuzzy Logic Method: Lighting Control Design, Mamdani Fuzzy Logic, Corn Fodder - susilo; Adi Mulyadi; Ratna Mustika Yasi (Journal of Educational Engineering and Environment, 2025)
This paper discusses the design and implementation of ultraviolet light control in corn fodder. The problem with corn fodder is that temperature and humidity and inappropriate lighting can trigger the growth of mold. The ultraviolet light illumination control system method uses a fuzzy logic method to control ultraviolet light illumination. So it affects temperature and humidity, as well as growth of corn fodder. The results of the comparison of the Mamdani fuzzy control system using Matlab and Arduino applications to control corn fodder illumination obtained defuzification values (0.5, 2.5, 6.5). The implementation of the Mamdani fuzzy logic control system affects the light, temperature and humidity, as well as the height and weight of the corn fodder with a definition error of 0.5%. Lighting 5 hours/day on a full spectrum grow light (380nm-730nm) with a light intensity of 2053lux, for 14 days produces a temperature of 27˚C and humidity of 93%, fodder height reaches 28cm with a total weight of 124 grams. Meanwhile, the grow light spectrum (450nm-460nm) with a light intensity of 1462.5 lux produces a temperature of 28˚C and humidity of 85%, the height of the fodder reaches 26.5cm with a total weight of 120 grams. Optimum lighting results were obtained in 5 hours of light with a full spectrum grow light lamp with a light intensity of 2053lux, for 14 days resulting in a temperature of 27˚C and humidity of 93%, the height of the fodder reached 28cm with a total weight of 124 grams.